Investigating The Effect of Soil Amendments on The Management of Fusarium Wilt of Tomato (Solanum lycopersicum L.) In Nigeria's Derived Savannah Transition Ecological Zone - Yekini, Buliaminu Adeniyi; Adesina , Jacobs Mobolade; Ogunoye, Olalekan Ajibolade (Journal of Tropical Plant Protection, 2025)
The study was conducted in Ishiagu, Nigeria, to evaluate the impact of soil amendments on tomato Fusarium wilt management during the 2022 and 2023 cropping seasons. Eight (8) treatments were distributed in a randomized complete block design and replicated three times. Topsoil at a depth of 0 to 15 cm were collected before application of treatments to determine physico-chemical characteristics of the soil. The collected data were subjected to ANOVA, with means separated using Tukey at p < 0.05. The results showed that the application of treatments had a non-significant (p < 0.05) effect on the percentage disease incidence. The disease incidence was consistently highest in untreated plots, reaching 61.89% in 2022 and 68.76% in 2023, while treated plots showed the lowest incidence, with 18.87% in 2022 and 18.09% in 2023. Similarly, the result of the disease severity ranged from 2.00-4.67. Treated plots consistently yielded higher harvested weights across both years, with pig manure treatments achieving the highest results (1101.67 g in 2022 and 1088.33 g in 2023), while untreated plots had the lowest yields (191.33 g in 2022 and 405.67 g in 2023). Therefore, combined application of Gmelina ash and palm bunch ash as an organic amendment, could be an alternative means of managing the Fusarium wilt and increase the yield of tomato by the small-scale farmers.